2011
DOI: 10.1007/s12975-011-0088-y
|View full text |Cite
|
Sign up to set email alerts
|

Biological Features of Human Bone Marrow Stromal Cells (hBMSC) Cultured with Animal Protein-Free Medium—Safety and Efficacy of Clinical Use for Neurotransplantation

Abstract: The donor cell culture in animal serum-free medium is quite important for the clinical application of cell transplantation therapy. This study was aimed to test the hypothesis that the human bone marrow stromal cells (hBMSC) expanded with fetal calf serum (FCS)-free, platelet lysate (PL)-containing medium retain their biological features favoring central nervous system regeneration. The hBMSC were cultured with 5% PL or 10% FCS. Their phenotypes were analyzed with flow cytometry, and their production of growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…In our previous study, no significant differences were observed between hBMSCs cultured using 5% PL and using 10% FCS [17]. In the present study, although the concentration of PL was changed to 10%, we confirmed that the hBMSCs were identical for surface markers.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our previous study, no significant differences were observed between hBMSCs cultured using 5% PL and using 10% FCS [17]. In the present study, although the concentration of PL was changed to 10%, we confirmed that the hBMSCs were identical for surface markers.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, our previous report showed that the concentration of human BDNF, which was derived from PL, markedly decreased in the medium after hBMSC culture. These results strongly suggested that the cultured hBMSCs may consume human BDNF for their survival and proliferation [17]. In the present study, we found that the content of these growth factors in each PL was relevant to the amount of platelets in original PC.…”
Section: Discussionsupporting
confidence: 57%
“…It is suggested that cell culture with PL supplementation does not change the expression of surface markers on cultured cells compared to that in cultures supplemented with FBS [634]. Most importantly, these cells retain their biological features, such as their growth and differentiation potential favoring target tissue regeneration [634,635].…”
Section: Formulations Enriched With Endogenous Growth Factorsmentioning
confidence: 99%
“…It is suggested that cell culture with PL supplementation does not change the expression of surface markers on cultured cells compared to that in cultures supplemented with FBS [634]. Most importantly, these cells retain their biological features, such as their growth and differentiation potential favoring target tissue regeneration [634,635]. In recent years, cumulative evidence has strongly indicated that human PL-supplemented media not only preserve cell phenotypes and shorten culture time by increasing the cells' growth rate but also maintain the cells' multilineage differentiation capacity and can give rise to osteoblasts, chondrocytes, adipocytes, neurons and astrocytes, among others [630,634638].…”
Section: Formulations Enriched With Endogenous Growth Factorsmentioning
confidence: 99%
See 1 more Smart Citation